PASANG SURUT REFORMASI BIROKRASI DALAM TRANSISI DEMOKRASI INDONESIA - Afala, La Ode Machdani (Faculty of Social and Political Science Universitas Brawijaya, 2017)
This study attempts to explain dilemmas in bureaucracy after the decline of New Order regime. Attempting bureaucracy reform is one of important agendas to find new format of better bureaucracy as well as to support democratic transition process in Indonesia. For that, specifically this study highlights relation between implementation of bureaucracy reform and development of democracy in purpose to create professional and effective bureaucracy. This study concludes that implementation of bureaucracy reform has yet been implemented effectively in creating professional bureaucracy. It is caused by some factors such as; the first is low of bureaucracy management quality and bureaucrat professionalism relating with integrity and technical ability. The some factors are implication of continuing of patrimonial legacy from New Order regime. The second, the presence of democracy in other side becomes a new mechanism for making bureaucracy as power machine by a group of people, politicians as well as bureaucrats.